High-durability recycled concrete and preparation method thereof
By using a modified emulsion to treat the regenerated coarse aggregate and adding Bacillus granules in the regenerated concrete, the problem of insufficient strength and durability of the regenerated concrete is solved, and high performance and high durability of regenerated concrete is achieved.
Patent Information
- Application Number
- CN202510170557.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-15
AI Technical Summary
The existing recycled concrete has low strength and poor durability, which limits its application in construction projects.
The ratio of high content of regenerated coarse aggregate is used to treat waste concrete by modifying emulsions (such as polyurea emulsion or polyurea-maleic anhydride composite emulsion), reducing its water absorption rate, improving mechanical properties, and adding Bacillus giant granules to the regenerated coarse aggregate to accelerate CaCO3 deposition and crack repair.
It significantly improves the mechanical properties and durability of recycled concrete, enhances its anti-chlorine ion penetration properties, and extends its service life.
Smart Images

Figure BDA0005273888310000131 
Figure BDA0005273888310000141 
Figure BDA0005273888310000142
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete preparation, and in particular to a high-durability recycled concrete and a preparation method thereof. Background Art
[0002] Recycled concrete refers to concrete that uses recycled aggregate as aggregate. Recycled aggregate is usually processed from solid waste such as waste bricks, waste concrete, and waste mortar. Using recycled aggregate to produce recycled concrete can reduce the demand for natural aggregates in construction projects, which is conducive to reducing the mining of natural aggregates. It is one of the harmless disposal methods for solid waste and is of great significance to protecting the natural environment.
[0003] However, the recycled concrete aggregate obtained after the crushing of waste concrete and waste bricks has too many edges and corners, and most of the recycled aggregates are needle-shaped. In addition, tiny cracks will appear inside the aggregates during the crushing process of the recycled aggregates. At the same time, part of the old mortar will generally adhere to the surface of the recycled aggregates, making the recycled aggregates have high water absorption, high porosity, and low apparent density compared to natural aggregates. These characteristics of recycled aggregates lead to lower strength and poor durability of recycled concrete, which restricts the application of recycled concrete. Summary of the invention
[0004] The purpose of the present invention is to provide a highly durable recycled concrete and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a highly durable recycled concrete, comprising the following raw materials in parts by weight: 330-350 parts of cement, 700-750 parts of natural fine aggregate, 1120-1150 parts of coarse aggregate and 3.8-4.2 parts of water reducing agent;
[0007] The coarse aggregate comprises the following raw materials in percentage by mass: 40-70% natural coarse aggregate and 30-60% recycled coarse aggregate;
[0008] The recycled coarse aggregate includes the following raw materials: waste concrete and modified emulsion;
[0009] The modified emulsion is a polyurea emulsion or a polyurea-maleic anhydride composite emulsion;
[0010] The concentration of the modified latex is 2-4 wt.%.
[0011] Polyurea emulsion or polyurea-maleic anhydride composite emulsion can fill the pores of waste concrete, can wrap the waste concrete, reduce the water absorption rate of the waste concrete, and improve the mechanical properties of the waste concrete.
[0012] Polyurea emulsion or polyurea-maleic anhydride composite emulsion has the advantages of light weight, good toughness, strong impact resistance and good durability (as reflected by frost resistance test), and has good application prospects in road projects with high requirements for impact resistance and durability.
[0013] Furthermore, the method for preparing the recycled coarse aggregate comprises:
[0014] The waste concrete is immersed in the modified emulsion, subjected to pressure treatment, taken out and dried to obtain the recycled coarse aggregate.
[0015] Furthermore, the preparation method of the polyurea-maleic anhydride composite emulsion comprises:
[0016] (1) mixing 2,4-toluene diisocyanate and amino-terminated polyether in the form of a solution, heating and reacting, and obtaining a polyurea prepolymer solution;
[0017] (2) adding an initiator and an emulsion of maleic anhydride monomer to a polyurea prepolymer solution, heating the solution for reaction, and obtaining the polyurea-maleic anhydride composite emulsion.
[0018] Further, the ratio of the molar number of isocyanate groups in the 2,4-toluene diisocyanate to the molar number of terminal amino groups in the terminal amino polyether is (0.9-1): (1-1.2);
[0019] The molar ratio of the 2,4-toluene diisocyanate to the maleic anhydride monomer is (0.8-1.0): (0.8-1.0);
[0020] And / or, the amount of the initiator used is 0.5-0.7% of the mass of 2,4-toluene diisocyanate.
[0021] Furthermore, in step (1), the heating reaction temperature is 80-90°C and the time is 3-4h;
[0022] In step (2), the heating reaction temperature is 50-60° C. and the time is 4-6 hours.
[0023] Furthermore, the raw material of the recycled coarse aggregate also includes Bacillus megaterium particles;
[0024] The mass ratio of the waste concrete to the Bacillus megaterium particles is 100:(1-1.5).
[0025] Furthermore, the method for preparing the recycled coarse aggregate comprises:
[0026] A. Bacillus megaterium is made into a bacterial suspension, and then porous activated carbon is added, vacuum impregnation is performed, and then filtration is performed, and low-temperature drying is performed to obtain a microbial complex;
[0027] B. mixing the microbial complex, soybean powder, starch and peanut powder evenly, and granulating to obtain Bacillus megaterium granules;
[0028] C. mixing the waste concrete and the Bacillus megaterium particles uniformly and then allowing the mixture to stand to obtain modified waste concrete;
[0029] D. Immersing the modified waste concrete in the modified emulsion, subjecting it to pressure treatment, taking it out and drying it, thereby obtaining the recycled coarse aggregate.
[0030] Furthermore, the dosage ratio of the bacterial suspension to the porous activated carbon is 100 mL: 5 g;
[0031] The vacuum impregnation pressure is 0.05-0.08 MPa, and the pressure holding time is 10 min;
[0032] The mass ratio of the microbial complex, soybean powder, starch and peanut powder is 10:15:20:15;
[0033] The particle size of the granulation is 2 to 3 mm;
[0034] The standing time is 5 to 8 days.
[0035] Bacillus megaterium can produce metalloenzymes to accelerate the conversion of CO2 to HCO 3- The conversion process between them can increase the CaCO3 deposition rate, improve the rate of repairing cracks in abandoned concrete, and improve the performance of abandoned concrete.
[0036] The second technical solution of the present invention is a method for preparing the above-mentioned highly durable recycled concrete, comprising the following steps:
[0037] After the coarse aggregate and the additional water are mixed evenly, cement, natural fine aggregate, water reducing agent and water are added, mixed evenly and then cured to obtain the highly durable recycled concrete.
[0038] Furthermore, the water-cement ratio of the high-durability recycled concrete is 0.40-0.45.
[0039] The water used to control the ash ratio to 0.40-0.45 does not include additional water. The purpose of adding additional water is that the recycled coarse aggregate in the coarse aggregate has a high water absorption rate and a certain amount of water needs to be added.
[0040] The present invention discloses the following technical effects:
[0041] The high-durability recycled concrete of the invention has excellent mechanical properties and durability, and has good resistance to chloride ion penetration.
[0042] The present invention can improve the utilization ratio of waste concrete while ensuring the mechanical properties of concrete. DETAILED DESCRIPTION
[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0044] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0048] 1. Problem raised and research significance
[0049] With the rapid development of industry and the continuous advancement of urbanization, the existing stock of industrial solid waste and construction waste is growing at a rapid rate. Most solid waste is piled up or buried, with low utilization rate, which brings serious pollution to the environment. Faced with the increasingly scarce social resources, especially the tense situation of non-renewable resources, it is urgent to save and rationally use resources, and continue to explore new resources as alternatives. In this context, "turning waste into treasure" has become an important one among a series of effective measures.
[0050] Recycled concrete technology can effectively solve a series of problems caused by construction waste and natural resource shortages. The core of recycled concrete technology is to convert waste concrete into recycled aggregates, which are then used in the configuration of concrete. On the one hand, recycled concrete can solve the problem of handling a large amount of waste concrete, minimize the adverse impact of construction waste on the environment, and make the concrete form a closed loop from production-put into use-waste recycling to being configured into concrete again after being processed by recycled concrete technology. On the other hand, the configuration of concrete with recycled aggregates instead of natural aggregates can reduce the demand for natural sand and gravel in the civil engineering field and solve the problem of shortage of natural resources. However, recycled aggregates will produce internal microcracks during the crushing production process, and the surface will also absorb old mortar, which leads to the obvious characteristics of recycled aggregates compared with natural aggregates, such as large porosity, high water absorption and large crushing value. Therefore, the use of special methods to improve the mechanical properties of recycled aggregates is helpful for promotion and application in actual engineering. At present, there are three main commonly used improvement methods: optimization of mix ratio method, strengthening of recycled aggregate method and fiber composite modification method.
[0051] (II) Research progress at home and abroad
[0052] (1) Performance of recycled concrete
[0053] Scholars at home and abroad have compared the mechanical properties of recycled concrete and ordinary concrete and reached a relatively consistent conclusion that the mechanical properties of recycled concrete are weaker than those of ordinary concrete.
[0054] The test results of OAU Uche (OAU Uche. Influence of recycled concrete aggregate (RCA) on compressive strength of plain concrete. Wilolud Online Journals, 2008.) show that when the recycled aggregate replacement rate is 100%, the compressive strength of concrete can drop by 33%. Sami W. Tabsh et al. (Sami W. Tabsh, Akmal S. Abdelfatah. Effect of recycled concrete aggregates on strength properties of concrete [J]. Construction & Building Materials, 2009, 23 (2): 1163-1167.) found that the strength of recycled concrete is 10-25% lower than that of ordinary concrete. Rahal KN et al. (Rahal K N, Alrefaei Y T. Shear Strength of Longitudinally Reinforced Recycled Aggregate Concrete Beams[J]. Engineering Structures, 2017, 145(aug.15):273-282.) conducted an experimental study on the shear strength of longitudinal reinforced concrete beams with different replacement rates. The results showed that the addition of recycled aggregate reduced the shear strength of the beams by 13 to 18%. H Ma (Ma H, Dong J, Y Liu, et al. Cyclic loading tests and shear strength of composite joints with steel-reinforced recycled concrete columns and steel beams[J]. Engineering Structures, 2019, 199(Nov.15):109605.1-109605.16.) conducted cyclic loading tests on 8 composite nodes (5 internal nodes and 3 external nodes) under cyclic loading. The test results showed that with the increase of the replacement rate of recycled coarse aggregate, the bearing capacity and stiffness of the nodes gradually decreased, and the ductility and energy consumption of the nodes also decreased slightly.The test results of Tabsh et al. (Tabsh SW, Abdelfatah AS. Effect of Recycled Concrete Aggregates on Strength Properties of Concrete [J]. Construction and Building Materials, 2009, 23 (2): 1163-1167.) show that the splitting tensile strength of recycled aggregate concrete is about 10% to 25% lower than that of ordinary concrete. The test results of Han Yuzhou et al. (Han Yuzhou, An Xuwen, Xiao Bei, et al. Experimental study on uniaxial compression of recycled aggregate concrete [J]. Journal of Yangtze River Scientific Research Institute, 2020, 37 (7): 135-139, 146.) show that the uniaxial compression peak strain of recycled concrete is less than that of ordinary concrete. Shi Xiaoshuang et al. (Shi Xiaoshuang, Wang Qingyuan, Qiu Cichang, Zhao Xiaolin. Experimental study on the performance of recycled concrete with different recycled aggregate replacement rates [J]. Journal of Sichuan University (Engineering Science Edition), 2010, 42(S1): 170-176.) found that the tensile and compressive properties of recycled aggregate concrete are weaker than those of ordinary concrete.
[0055] (2) Recycled concrete replacement rate
[0056] Relevant studies have shown that due to the presence of recycled coarse aggregate, the tensile strength, compressive strength, chloride ion permeability resistance and frost resistance of recycled concrete are weakened to varying degrees, and the greater the aggregate replacement rate, the weaker the performance.
[0057] Limbachiya MC et al. (Limbachiya MC, Leelawat T, Dhir RK Use of recycled concrete aggregate in high-gh-strength concrete [J]. Materials and Structures, 2000, 33 (10): 574-580.) found that when the content of recycled coarse aggregate exceeded 30%, the compressive strength of the specimens gradually decreased with the increase of recycled aggregate content. Ashish Shrimali et al. (Ashish Shrimali et al. Behavior of Concrete Utilizing Recycled Aggregate–A Review [J]. International Journal of Engineering Research and Applications 2017, 07 (1): 72-79.) came to the same conclusion: when the content of recycled aggregate in concrete is higher than 30%, the mechanical properties and durability of concrete will be reduced. Bairagi NK, Ravande Kishore, Pareek VKB Behavior of concrete with different proportions of natural and recycled aggregates. Resources [J]. Conservation and Recycling, 1993, 9 (1): 109-126.) found that the stress-strain curve of concrete had basically the same trend with different replacement rates of recycled aggregate. Topcu IB (Topcu IB, Guncan NFUsing waste concrete as aggregate [J]. Cement and Concrete Research, 1995, 25 (7): 1385-1390.) and Xiao Jianzhuang et al. (Xiao Jian Zhuang, Li Jiabin. Mechanical properties of recycled aggregate concrete under axial loading [J]. Cement and Concrete Research, 2005, 35 (6): 1187-1194.) found that with the increase of the replacement rate of recycled aggregate, the peak stress of recycled concrete decreased, but the peak strain increased.The experiment conducted by Xiao Kaitao et al. (Xiao Kaitao, Lin Zongshou, Wan Huiwen, Yang Liyuan. Study on chloride ion permeability of recycled concrete [J]. Shandong Building Materials, 2004 (01): 31-33.) shows that when the recycled aggregate content is greater than 50%, the more recycled aggregate content, the weaker the concrete's resistance to chloride ion penetration. Li Wenxia et al. (Li Wenxia, Zhang Xiong, Liu Xin. Discussion on the relationship between recycled aggregate replacement rate, paste content, apparent density and water absorption rate in recycled concrete [J]. Concrete, 2009 (10): 60-63.) found through experimental research that the water absorption rate of recycled aggregate has a significant positive correlation with the replacement rate, and has a very strong linear relationship. The experimental results of Abdurrahmaan Lotfy et al. (Abdurrahmaan Lotfy, Mahmoud Al-Fayez. Performance evaluation of structural concrete using controlled quality coarse and fine recycled concrete aggregate[J]. Cement and Concrete Composites, 2015, 61.) also showed that compared with ordinary concrete, the water absorption capacity of recycled concrete increases with the increase of aggregate replacement rate.
[0058] (3) Methods for improving the performance of recycled concrete
[0059] At present, there are three main commonly used improvement methods: optimizing mix ratio, strengthening recycled aggregate and fiber composite modification.
[0060] The optimization mix ratio method is to make up for the shortcomings of recycled aggregates through the mix ratio. Although this method is traditional and reliable, after increasing the amount of cement, the shrinkage deformation of recycled concrete increases, it is easy to crack, the structural applicability and durability decrease, and the construction cost increases.
[0061] Strengthening recycled aggregate is to use physical or chemical media to remove cement mortar attached to its surface or substances generated by reaction with it, such as carbonate, gel, etc., to improve the physical and mechanical properties of recycled aggregate. In this regard, specific measures used include heating and grinding, ultrasonic cleaning, PVA solution wrapping treatment, CO2 gas strengthening, etc. In general, the above measures can improve the internal pore structure of recycled aggregate and essentially improve the properties of recycled aggregate, but the strengthening technology requires large investment in equipment or materials, and the strengthening cycle is long, and its application in actual engineering has certain limitations.
[0062] The fiber composite modification method generally incorporates various fibers to improve the strength and toughness of recycled concrete, such as PVA fiber, carbon fiber, steel fiber, etc. PVA fiber can improve the strength and durability of recycled concrete, but due to the small length of PVA fiber, it is not suitable for strengthening recycled concrete with large particle size. Carbon fiber has good toughening effect, but it is expensive. Steel fiber can increase the flexural strength and toughness of recycled concrete, but it cannot increase the compressive strength.
[0063] The “parts” described in the following examples are all “parts by mass”.
[0064] The raw materials used in the specific implementation of the present invention are as follows:
[0065] (1) The natural fine aggregate is natural river sand with a fineness modulus of 3.1 and an apparent density of 2580 kg / m 3 , bulk density is 1615kg / m 3 , mud content is 1.5% and water absorption rate is 1.4%.
[0066] (2) Natural coarse aggregate is natural crushed stone with a particle size of 5 to 20 mm and an apparent density of 2685 kg / m 3 , bulk density is 1627kg / m 3 , mud content is 0.36% and water absorption rate is 0.8%.
[0067] 5mm≤particle size<10mm, accounting for 13.80wt.%;
[0068] 10mm≤particle size<15mm, accounting for 56.35wt.%;
[0069] Particle size 15mm≤≤20mm, accounting for 29.85wt.%.
[0070] (3) Waste concrete, particle size 5-20 mm, apparent density 2437 kg / m 3 , bulk density is 1395kg / m 3 , mud content is 0.75% and water absorption is 4.5%.
[0071] 5mm≤particle size<10mm, accounting for 12.55wt.%;
[0072] 10mm≤particle size<15mm, accounting for 55.27wt.%;
[0073] Particle size 15mm≤≤20mm, accounting for 32.18wt.%.
[0074] (4) The water reducer is a polycarboxylic acid high efficiency water reducer.
[0075] (5) The cement is P·O 42.5 cement. Before the test, the technical indicators of cement were tested according to GB175-2020, and all parameter indicators met the requirements of the standard.
[0076] (6) The amino-terminated polyether is amino-terminated polyether (polyetheramine) D2000.
[0077] The Bacillus megaterium used in the specific embodiment of the present invention is purchased from the China Industrial Microbiological Culture Collection Center, and the product number of the Bacillus megaterium is CICC 22681.
[0078] Example 1
[0079] A method for preparing highly durable recycled concrete:
[0080] (1) High durability recycled concrete, composed of the following raw materials in parts by weight: 350 parts of cement, 750 parts of natural fine aggregate, 1120 parts of coarse aggregate (composed of natural coarse aggregate and recycled coarse aggregate in a mass ratio of 4:6), 15 parts of additional water, 3.8 parts of water reducing agent, and 140 parts of water.
[0081] (2) Preparation method of recycled coarse aggregate
[0082] A. Preparation of polyurea emulsion:
[0083] Preparation of isocyanate (component A): 280g of polypropylene glycol (weight average molecular weight Mw = 2000) was placed in a dry three-necked flask, heated to 120°C for vacuum dehydration for 6h, cooled to 40°C, and 20g of 4,4-diphenylmethane diisocyanate was added thereto. The mixture was stirred and heated to 120°C under nitrogen protection, and reacted for 3h. After the reaction time was over, the system was collected when it dropped to 45°C to obtain isocyanate (component A).
[0084] Preparation of amino compound (component B): polyetheramine (weight average molecular weight Mw = 2000) is placed in a dry three-necked flask, epoxy resin curing agent (polyamide, weight average molecular weight Mw = 400), diethyltoluenediamine, N, N-dialkylmethyldiamine are added thereto, and the mixture is stirred and heated to 85°C, and reacted for 2 hours to obtain amino compound (component B);
[0085] The mass ratio of polyetheramine, polyether polyamine, epoxy resin curing agent, diethyltoluenediamine and N,N-dialkylmethyldiamine is 2.5:2:2:2.4.
[0086] Preparation of polyurea: Component A and component B were mixed in a mass ratio of 1:1, cured for 10 hours and then dried to obtain polyurea.
[0087] The polyurea was added into water and dispersed at a high speed (rotation speed of 2000 r / min) for 10 min to obtain a modified emulsion with a concentration of 3 wt. % (polyurea emulsion with a concentration of 3 wt. %).
[0088] B. Immerse the waste concrete in a modified latex with a concentration of 3 wt.%, pressurize it to 5 MPa for 10 minutes, take it out and dry it (temperature is 40° C.) to obtain recycled coarse aggregate.
[0089] (3) After the coarse aggregate and the additional water are mixed evenly, cement, natural fine aggregate, water reducer and water are added, the mixture is evenly poured into a mold with a size of 100×100×100 mm, and the mixture is left to stand for 24 h before demolding and curing in a curing room (according to standard GB / T50081-2019) to obtain highly durable recycled concrete.
[0090] Example 2
[0091] The same as Example 1, except that the coarse aggregate is composed of natural coarse aggregate and recycled coarse aggregate in a mass ratio of 7:3.
[0092] Example 3
[0093] Same as Example 1, except that the polyurea emulsion with a concentration of 3 wt.% is replaced by a polyurea-maleic anhydride composite emulsion with a concentration of 3 wt.%.
[0094] The preparation method of polyurea-maleic anhydride composite emulsion (modified emulsion) is as follows:
[0095] A. Disperse 2,4-toluene diisocyanate and amino-terminated polyether (the ratio of the molar number of isocyanate groups in 2,4-toluene diisocyanate to the molar number of terminal amino groups in the amino-terminated polyether is 1:1.2) in acetone respectively, then mix them evenly, and heat them for reaction (the heating reaction temperature is 90°C and the time is 3h) to obtain a polyurea prepolymer solution.
[0096] B. Add the initiator and the emulsion of maleic anhydride monomer to the polyurea prepolymer solution, heat the reaction (the heating reaction temperature is 55° C., the time is 5 hours), and adjust the solid content to 3 wt.%, to obtain a polyurea-maleic anhydride composite emulsion with a concentration of 3 wt.%.
[0097] The preparation of the emulsion of maleic anhydride monomer is as follows: maleic anhydride monomer and water are mixed at a mass ratio of 1:10 and then dispersed uniformly at high speed (rotating speed of 2000 r / min, time of 10 min) to obtain the emulsion of maleic anhydride monomer;
[0098] The amount of initiator used is 0.6% of the mass of 2,4-toluene diisocyanate;
[0099] The molar ratio of 2,4-toluene diisocyanate to maleic anhydride monomer is 0.8:1.0.
[0100] Example 4
[0101] The same as Example 3, except that Bacillus megaterium particles are added during the preparation of the recycled coarse aggregate.
[0102] Preparation of recycled coarse aggregate:
[0103] Ⅰ. Bacillus megaterium was inoculated into liquid culture medium for activation culture and then fermented to obtain bacterial counts of 1.0×10 9 cfu / mL of Bacillus megaterium liquid; wherein the components of the liquid culture medium are: 5.0 g / L peptone, 3.0 g / L beef extract and 5.0 g / L sodium chloride, pH 7.0; wet heat sterilization for 20 minutes.
[0104] Porous activated carbon was added to the Bacillus megaterium liquid (the ratio of the Bacillus megaterium liquid to the porous activated carbon was 100 mL: 5 g), vacuum impregnation was performed (the vacuum impregnation pressure was 0.05 MPa, and the pressure holding time was 10 min), and then filtration was performed, and low-temperature drying (temperature was 40° C.) was performed to obtain a microbial composite;
[0105] Among them, the specific surface area of porous activated carbon is 2100m 2 / g, the average pore diameter is 0.8nm and the porosity is 45%.
[0106] Ⅱ. The microbial complex, soybean powder, starch and peanut powder were mixed uniformly in a mass ratio of 10:15:20:15, and granulated (the particle size was 2 to 3 mm) to obtain Bacillus megaterium particles;
[0107] Among them, the particle sizes of soybean flour, starch and peanut cake flour are all 400 meshes.
[0108] Ⅲ. The water content of the waste concrete was adjusted to 10%, and then Bacillus megaterium particles were added (the mass ratio of waste concrete and Bacillus megaterium particles was 100:1.2), mixed evenly and allowed to stand for 6 days to obtain modified waste concrete;
[0109] IV. The modified waste concrete is immersed in the modified latex, pressurized to 5MPa for 10min, taken out and dried (temperature is 40°C) to obtain recycled coarse aggregate.
[0110] Comparative Example 1
[0111] The same as Example 1, except that the polyurea emulsion with a concentration of 3 wt.% is replaced by a polyvinyl alcohol solution with a concentration of 3 wt.% (the weight average molecular weight of the polyvinyl alcohol is Mw=2000).
[0112] Comparative Example 2
[0113] The same as Example 1, except that the polyurea emulsion with a concentration of 3 wt.% is replaced by an acrylic acid solution with a concentration of 3 wt.%.
[0114] Comparative Example 3
[0115] The same as Example 1, except that the recycled coarse aggregate is waste concrete (without any treatment).
[0116] Comparative Example 4
[0117] The same as Example 1, except that the concrete is composed of the following raw materials in parts by weight: 350 parts of cement, 750 parts of natural fine aggregate, 1120 parts of coarse aggregate (natural coarse aggregate), 3.8 parts of water reducer, and 140 parts of water.
[0118] The preparation method is as follows: coarse aggregate, cement, natural fine aggregate, water reducer and water are uniformly mixed, poured into a mold with a size of 100×100×100 mm, left to stand for 24 hours, then demolded, and placed in a curing room for curing (according to standard GB / T 50081-2019) to obtain concrete.
[0119] Effect Example 1
[0120] The compressive strength of the specimens (size 100×100×100mm) cured for different times was measured according to standard GB / T 50081-2019. The results are shown in Table 1.
[0121] Table 1 Compressive strength of specimens
[0122]
[0123] Effect Example 2
[0124] According to the standard GB / T50082-2009, the frost resistance test is carried out. Four days before the specified age (28 days), the specimen (size 100×100×100mm) is immersed in water at 20±2℃, and the water surface is at least 20mm higher than the specimen (for specimens maintained in water, they can be directly used for testing after reaching the specified age). After immersion for 4 days, the freeze-thaw test is carried out. Each freeze-thaw cycle should be completed within 4h, and the time used for thawing should not be less than 1 / 4 of the entire freeze-thaw time. At the end of freezing and thawing, the center temperature of the specimen should be controlled at minus 18±2℃ and 5±2℃ respectively. The center temperature should be based on the actual measured temperature of the temperature measurement standard specimen. In the test chamber, the time taken for each specimen at each position to drop from 3℃ to -16℃ shall not be less than 1 / 2 of the entire freezing time, and the time taken for each specimen to rise from minus 16℃ to 3℃ shall not be less than 1 / 2 of the entire thawing time. The temperature difference between the inside and outside of the specimen should not exceed 28℃. The transition time between freezing and thawing should not exceed 10 minutes.
[0125] The mass change rate is calculated as follows:
[0126]
[0127] Among them, W n is the mass change rate of the specimen after n freeze-thaw cycles (%);
[0128] m0 is the mass of the specimen before the freeze-thaw test (kg);
[0129] m n is the mass of the specimen after n freeze-thaw cycles (kg);
[0130] The average value of three specimens is taken as the test result, and the result is calculated with an accuracy of 0.1%.
[0131] Table 2 Mass loss rate of specimens (%)
[0132]
[0133] Effect Example 3
[0134] According to the standard NT BUILD 492, the chloride ion diffusion coefficient of the specimens cured for 28 days was measured. The results are shown in Table 3.
[0135] Table 3 Chloride ion diffusion coefficient of the specimens
[0136] Grouping <![CDATA[Chloride ion diffusion coefficient (m 2 / s)]]> Example 1 <![CDATA[3.25×10 -12 ]]> Example 2 <![CDATA[2.87×10 -12 ]]> Example 3 <![CDATA[2.42×10 -12 ]]> Example 4 <![CDATA[2.33×10 -12 ]]> Comparative Example 1 <![CDATA[11.57×10 -12 ]]> Comparative Example 2 <![CDATA[12.36×10 -12 ]]> Comparative Example 3 <![CDATA[17.23×10 -12 ]]> Comparative Example 4 <![CDATA[7.52×10 -12 ]]>
[0137] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A highly durable recycled concrete, characterized in that: The raw materials include the following parts by weight: 330-350 parts of cement, 700-750 parts of natural fine aggregate, 1120-1150 parts of coarse aggregate and 3.8-4.2 parts of water reducing agent; The coarse aggregate comprises the following raw materials in percentage by mass: 40-70% natural coarse aggregate and 30-60% recycled coarse aggregate; The recycled coarse aggregate includes the following raw materials: waste concrete and modified emulsion; The modified emulsion is a polyurea emulsion or a polyurea-maleic anhydride composite emulsion; The concentration of the modified latex is 2-4 wt.%.
2. The highly durable recycled concrete according to claim 1, characterized in that: The method for preparing the recycled coarse aggregate comprises: The waste concrete is immersed in the modified emulsion, subjected to pressure treatment, taken out and dried to obtain the recycled coarse aggregate.
3. The highly durable recycled concrete according to claim 1, characterized in that: The preparation method of the polyurea-maleic anhydride composite emulsion comprises: (1) mixing 2,4-toluene diisocyanate and amino-terminated polyether in the form of a solution, heating and reacting, and obtaining a polyurea prepolymer solution; (2) adding an initiator and an emulsion of maleic anhydride monomer to a polyurea prepolymer solution, heating the solution for reaction, and obtaining the polyurea-maleic anhydride composite emulsion.
4. The highly durable recycled concrete according to claim 3, characterized in that: The ratio of the molar number of isocyanate groups in the 2,4-toluene diisocyanate to the molar number of terminal amino groups in the terminal amino polyether is (0.9-1): (1-1.2); and / or, the molar ratio of the 2,4-toluene diisocyanate to the maleic anhydride monomer is (0.8-1.0):(0.8-1.0); And / or, the amount of the initiator used is 0.5-0.7% of the mass of 2,4-toluene diisocyanate.
5. The highly durable recycled concrete according to claim 3, characterized in that: In step (1), the heating reaction temperature is 80-90°C and the time is 3-4h; And / or, in step (2), the heating reaction temperature is 50-60° C. and the time is 4-6 hours.
6. The highly durable recycled concrete according to claim 1, characterized in that: The raw materials of the recycled coarse aggregate also include Bacillus megaterium particles; The mass ratio of the waste concrete to the Bacillus megaterium particles is 100:(1-1.5).
7. The highly durable recycled concrete according to claim 6, characterized in that: The method for preparing the recycled coarse aggregate comprises: A. Bacillus megaterium is made into a bacterial suspension, and then porous activated carbon is added, vacuum impregnation is performed, and then filtration is performed, and low-temperature drying is performed to obtain a microbial complex; B. mixing the microbial complex, soybean powder, starch and peanut powder evenly, and granulating to obtain Bacillus megaterium granules; C. mixing the waste concrete and the Bacillus megaterium particles uniformly and then allowing the mixture to stand to obtain modified waste concrete; D. Immersing the modified waste concrete in the modified emulsion, subjecting it to pressure treatment, taking it out and drying it, thereby obtaining the recycled coarse aggregate.
8. The highly durable recycled concrete according to claim 7, characterized in that: The dosage ratio of the bacterial suspension to the porous activated carbon is 100 mL: 5 g; And / or, the vacuum impregnation pressure is 0.05-0.08 MPa, and the pressure holding time is 10 min; And / or, the mass ratio of the microbial complex, soybean powder, starch and peanut powder is 10:15:20:15; And / or, the particle size of the granulation is 2 to 3 mm; And / or, the standing time is 5 to 8 days.
9. A method for preparing highly durable recycled concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: After the coarse aggregate and the additional water are mixed evenly, cement, natural fine aggregate, water reducing agent and water are added, mixed evenly and then cured to obtain the highly durable recycled concrete.
10. The preparation method according to claim 9, characterized in that: The water-cement ratio of the high-durability recycled concrete is 0.40-0.45.